The Effect of Audit Complexity, Time Budget Pressure and Work Pressure on Dysfunctional Audit Behavior with Locus of Control as Moderation - Siti, Siti; Annis Syahzuni, Barlia (Lafadz Jaya Publisher, 2025)
This study examines the role of locus of control as a moderating variable in the relationship between audit complexity, time budget pressure, and job stress on auditor dysfunctional behavior. Dysfunctional behavior in the context of auditing refers to actions that can damage the integrity and quality of audit results, such as delays in work, non-objective decision making, or neglect of proper audit procedures. Auditors often face challenges in the form of high task complexity, tight deadlines, and high job stress. The sample used was auditors working at a Public Accounting Firm in the Jakarta area. The sample of this study consisted of 125 respondents. Primary data analysis was carried out using the Structural Equation Modeling (SEM) method. The results of this study indicate that the time budget pressure variable has the greatest direct influence on auditor dysfunctional behavior. Then locus of control has the greatest direct influence on the relationship between audit complexity and auditor dysfunctional behavior. This study contributes to public accounting firm employees in maintaining and improving their audit quality, somewhat avoiding auditor dysfunctional behavior, which can be seen from several factors, namely prioritizing larger teams with stricter levels of supervision, so that auditors have an incentive to comply with proper audit procedures rather than taking dysfunctional actions. Then face the pressure to develop better individual skills. For further research, researchers plan to expand the research area and look for objects in other fields.